Development of a Digital Game-Based Word-Guessing Learning for Ice-Breaking Activities - Muh Dliyaul Haq (Gameology and Multimedia Expert, 2026)
Student disengagement remains a persistent challenge in primary education, particularly in classrooms dominated by passive instructional approaches. This study aimed to develop and evaluate a digital word-guessing game designed as an ice-breaking learning activity using an AI-assisted rapid prototyping approach. The game was developed using Canva AI as a no-code platform to enable efficient and iterative design. User testing was conducted with 30 primary school students in Grades 4–6 to examine students’ perceptions of the game across seven dimensions: collaboration, affective engagement, cognitive agility, creative thinking, attention/focus, behavioral engagement, and usability. Data were collected using a five-point Likert-scale questionnaire and supported by classroom observations. The results showed consistently high mean scores across all assessed aspects, indicating that the game was perceived as enjoyable, easy to use, and effective in promoting teamwork, sustained attention, and rapid thinking. The findings demonstrate that short-duration digital games can function as effective pedagogical micro-interventions when systematically designed and embedded within classroom routines. This study contributes to the literature by reconceptualizing ice-breaking activities as intentional digital learning tools and by proposing a replicable AI-assisted rapid prototyping framework for developing scalable, classroom-ready educational games without advanced programming expertise.